Prevalence of oral frailty in community-dwelling older adults: a systematic review and meta-analysis - Dou, Jun-kai; Liu, Huan; Mei, Yan; Wang, Song; Zhang, Ying; Zhao, Shao-hua; Shi, Xue-zhi (Frontiers in Public Health, 2025)
BackgroundOlder adults are vulnerable to oral frailty due to factors such as age, education level, physical condition, and limited access to medical resources. Given that oral frailty can lead to adverse outcomes and is often overlooked by policymakers and health professionals, it is important to understand the current state of oral frailty among community-dwelling older adults.DesignSystematic review and meta-analysis.MethodsTwo researchers independently conducted searches in seven databases, extracted data, and assessed the quality of eligible studies. Data from cross-sectional studies or cohort studies with a clear definition of oral frailty. Stata 14.0 was utilized to evaluate the overall prevalence of oral frailty, while Cochrane's Q, I2statistics were employed to assess statistical heterogeneity.ResultsA total of 15 studies were ultimately included in this analysis. The pooled prevalence of oral frailty among community-dwelling older adults was 32% (95% CI: 24%−40%, I2 = 98.9%, P < 0.001). By country, the prevalence was 53% (95% CI: 42%−65%) in China and 22% (95% CI: 19%−39%) in Japan. The incidence of oral frailty was 29% (95% CI: 18%−39%) among those aged 74 and over and 26% (95% CI: 16%−36%) among those under 74. The prevalence of oral frailty was 46% (95% CI: 31%−60%) as assessed by the OFI-8 scale, 18% (95% CI: 14%−22%) using the OF-6 scale, and 37% (95% CI: 34%−39%) with the OFI-5 scale. The rates of oral frailty reported before 2021 and between 2022–2024 were 17% (95% CI: 13%−21%) and 42% (95% CI: 31%−53%), respectively. The rate of oral frailty was 39% (95% CI: 23%−54%) for sample sizes ≤ 500, and 25% (95% CI: 16%−33%) for sample sizes >500. Univariate meta-regression analysis revealed that country, measurement method, and publication year might be sources of heterogeneity. Funnel plot analysis and Egger's test showed no significant publication bias among the eligible studies.ConclusionOur study found that oral frailty affects more than one in three older adults living in the community. This highlights the importance for policymakers and health professionals to screen early and implement effective measures to prevent oral frailty among older adults residing in community settings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#searchadvanced, identifier: CRD42024527800.